2003
DOI: 10.3349/ymj.2003.44.4.747
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of an Immunochromatographic Kit for the Detection of Antibody toPLASMODIUM VIVAXInfection in South Korea

Abstract: Malaria is a major parasitic disease in tropical areas. Three to five hundred million people suffer from the disease and it kill a million people per year. Blood smear observation was developed for the diagnosis of malaria, but the examination needs skilled experts and exact diagnosis is time consuming. A kit based on immunochromatography can be a reliable and rapid method for clinical diagnosis, even in the hands of inexperienced personnel. However, all such currently developed kits can only diagnose P. falci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Results showed that the novel kit developed in this study is more sensitive (98%) and specific (99.7%) than is SD BioLine Malaria P.f/P.v from Alere Inc. (95.1% sensitivity and 99.1% specificity), which uses the same target as that used in the novel kit. The diagnostic performance of the novel Malaria Pf/Pv Ab RDT is comparable or better than that of others presented in previous reports 21 , 48 , 49 , 51 , 52 , although most previous studies tested the reactivity of PfMSP1 19 or PvMSP1 19 recombinant proteins with ELISA and western blot analysis rather than RDT. The sensitivities ranged from 90~100% for vivax malaria 21 , 49 , 51 and 50~90.6% for falciparum malaria 21 , 51 .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Results showed that the novel kit developed in this study is more sensitive (98%) and specific (99.7%) than is SD BioLine Malaria P.f/P.v from Alere Inc. (95.1% sensitivity and 99.1% specificity), which uses the same target as that used in the novel kit. The diagnostic performance of the novel Malaria Pf/Pv Ab RDT is comparable or better than that of others presented in previous reports 21 , 48 , 49 , 51 , 52 , although most previous studies tested the reactivity of PfMSP1 19 or PvMSP1 19 recombinant proteins with ELISA and western blot analysis rather than RDT. The sensitivities ranged from 90~100% for vivax malaria 21 , 49 , 51 and 50~90.6% for falciparum malaria 21 , 51 .…”
Section: Discussionsupporting
confidence: 57%
“…The specificity was 50~98.3% for vivax malaria 21 , 49 , 51 and 50% for falciparum malaria 21 . One report described the development and evaluation of PvMSP1-based antibody RDT 52 . The sensitivity and specificity were 96.6% and 91.4%, respectively in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Other antigens were also shown to be markers of P. vivax infection, but only in single populations (PvMSP-3α, PvMSP-9 RIRII , PvDBP, and PvRBP1). Serosurveillance using PvCSP in Korea [63][64][65][66][67] and PvMSP-1 19 and PvAMA1 in Vanuatu [68], Cambodia [69], and Somalia [70] has been employed to successfully map P. vivax transmission, and data from this review support their use in serosurveillance campaigns. However, this review highlights that further studies, conducted in diverse geographical settings and including additional antigens, are needed to ensure the generalizability of results across different populations with variable P. vivax transmission.…”
Section: Discussionmentioning
confidence: 76%
“…The iFAT is difficult to apply to situations involving large numbers of samples, and although the ELiSA is sensitive and suitable for processing large amounts of samples, standardised commercial kits are lacking. Therefore, the use of an immunochromatographic test to detect malaria-specific antibodies may be an alternative technique for the processing of large numbers of samples, which is necessary for blood therapy services and epidemiological studies (Park et al 2003). The SD Bioline Malaria Pf/Pv (Standard Diagnostics, inc, Suwon, Korea) is a rapid test for the qualitative detection of igG, igM and igA antibodies specific for Plasmodium falciparum and P. vivax antigens.…”
mentioning
confidence: 99%